Challenging theocracy : ancient lessons for global politics - Tabachnick, David Edward, 1972-; Koivukoski, Toivo; Teixeira, Hermínio Meireles (University of Toronto Press, 2018)
Commonly perceived as a direct threat to the practice of liberal democracy, the global reemergence of theocratic claims to political rule is a misunderstood development of twenty-first century politics. Analyzing the relationship between religion and politics throughout the Middle East, Africa, and the United States, as well as classical and medieval political philosophical sources, Challenging Theocracy critiques the contemporary formation of theocracy. Providing an account of the origins and influence of theocracy, the chapters in this volume explore ancient texts that articulate the theocratic political ideas that continue to bubble under the surface of political life today. In an effort to consider how regimes extend beyond their immediate institutional and legal forms and find their foundation in timeless ideas, the contributors examine ancient and modern political thought to better understand their persistent power and impact on global politics.